CANCER OF THE FEMALE REPRODUCTIVE SYSTEM IN THE FAR EASTERN FEDERAL DISTRICT - V. P. Gordienko; S. N. Leontjeva; T. N. Korobkova (Сибирский онкологический журнал)
The aim of the study was to assess the incidence and mortality rates of female reproductive system cancer in the Far Eastern Federal District over the last ten years (2008–2017).Material and Methods. In our study we used statistical reports on the female reproductive system cancer incidence and mortality rates and 10-year follow-up data.Results. In 2017, 25155 new cases of female reproductive system cancer were diagnosed in the Far Eastern Federal District (26.6 % higher than in 2008). A total of 128776 patients (2.1 % of the population of the region) were followed up. Over the study period, there has been increase in the number of patients with stage I–II breast cancer (+4.8 %), cervical cancer (+6.3 %), uterine body (+3.9 %) and ovarian cancer (+5.7 %), with simultaneous reduction in the number of patients with advanced stages, except ovarian cancer (+5.0 %). For the past 10 years, cancer incidence rates have been steadily increasing, while cancer mortality rates have been decreasing with the exception of cervical cancer (+13.7 %). Morphological confirmation of the diagnosis (over 90 %) exceeded the national average ones. The number of patients followed-up for 5 or more years appeared to be lower than the average values in Russia; however the 1-year mortality rates after diagnosis improved. Ovarian cancer remains the most deadly of the gynecological cancers (22.9–27.9 %).Conclusion. Over the last ten years in the Far Eastern Federal District, in contrast to the overall decline in the mortality rates, there has been a steady increase in the incidence rates of female reproductive system cancer, except for cervical cancer.